Amphibian species traits, evolutionary history and environment predict Batrachochytrium dendrobatidis infection patterns, but not extinction risk. (3rd September 2017) - Greenberg, Dan A.; Palen, Wendy J.; Mooers, Arne Ø.
Abstract: The fungal pathogen Batrachochytrium dendrobatidis ( B. dendrobatidis ) has emerged as a major agent of amphibian extinction, requiring conservation intervention for many susceptible species. Identifying susceptible species is challenging, but many aspects of species biology are predicted to influence the evolution of host resistance, tolerance, or avoidance strategies towards disease. In turn, we may expect species exhibiting these distinct strategies to differ in their ability to survive epizootic disease outbreaks. Here, we test for phylogenetic and trait‐based patterns of B. dendrobatidis infection risk and infection intensity among 302 amphibian species by compiling a global data set of B. dendrobatidis infection surveys across 95 sites. We then use best‐fit models that associate traits, taxonomy and environment with B. dendrobatidis infection risk and intensity to predict host disease mitigation strategies (tolerance, resistance, avoidance) for 122 Neotropical amphibian species that experienced epizootic B. dendrobatidis outbreaks, and noted species persistence or extinction from these events. Aspects of amphibian species life history, habitat use and climatic niche were consistently linked to variation in B. dendrobatidis infection patterns across sites around the world. However, predicted B. dendrobatidis infection risk and intensity based on site environment and species traits did not reveal a consistent pattern between the predicted host disease mitigation strategy and extinction outcome. This suggests that either tolerant or resistant species may have no advantage in ameliorating disease during epizootic events, or that other factors drive the persistence of amphibian populations during chytridiomycosis outbreaks. These results suggest that using a trait‐based approach may allow us to identify species with resistance or tolerance to endemic B. dendrobatidis infections, but that this approach may be insufficient to ultimately identify species at risk of extinction from epizootics.